SPECT/CT Imaging, Biodistribution and Radiation Dosimetry of a 177Lu-DOTA-Integrin αvβ6 Cystine Knot Peptide in a Pancreatic Cancer Xenograft Model - Sachindra, Sachindra; Hellberg, Teresa; Exner, Samantha; Prasad, Sonal; Beindorff, Nicola; Rogalla, Stephan; Kimura, Richard; Gambhir, Sanjiv Sam; Wiedenmann, Bertram; Grötzinger, Carsten (Frontiers in Oncology, 2021)
Introduction Pancreatic ductal adenocarcinoma (PDAC) is one of the most aggressive malignant neoplasms, as many cases go undetected until they reach an advanced stage. Integrin αvβ6 is a cell surface receptor overexpressed in PDAC. Consequently, it may serve as a target for the development of probes for imaging diagnosis and radioligand therapy. Engineered cystine knottin peptides specific for integrin αvβ6 have recently been developed showing high affinity and stability. This study aimed to evaluate an integrin αvβ6-specific knottin molecular probe containing the therapeutic radionuclide 177Lu for targeting of PDAC. Methods The expression of integrin αvβ6 in PDAC cell lines BxPC-3 and Capan-2 was analyzed using RT-qPCR and immunofluorescence. In vitro competition and saturation radioligand binding assays were performed to calculate the binding affinity of the DOTA-coupled tracer loaded with and without lutetium to BxPC-3 and Capan-2 cell lines as well as the maximum number of binding sites in these cell lines. To evaluate tracer accumulation in the tumor and organs, SPECT/CT, biodistribution and dosimetry projections were carried out using a Capan-2 xenograft tumor mouse model. Results RT-qPCR and immunofluorescence results showed high expression of integrin αvβ6 in BxPC-3 and Capan-2 cells. A competition binding assay revealed high affinity of the tracer with IC50 values of 1.69 nM and 9.46 nM for BxPC-3 and Capan-2, respectively. SPECT/CT and biodistribution analysis of the conjugate 177Lu-DOTA-integrin αvβ6 knottin demonstrated accumulation in Capan-2 xenograft tumors (3.13 ± 0.63%IA/g at day 1 post injection) with kidney uptake at 19.2 ± 2.5 %IA/g, declining much more rapidly than in tumors. Conclusion 177Lu-DOTA-integrin αvβ6 knottin was found to be a high-affinity tracer for PDAC tumors with considerable tumor accumulation and moderate, rapidly declining kidney uptake. These promising results warrant a preclinical treatment study to establish therapeutic efficacy.